O30: EVALUATION OF AXILLARY LYMPH NODE METASTATIC BURDEN BY PREOPERATIVE ULTRASOUND. (27th April 2021) - Keelan, S; Sorensen, J; Downey, E; Hegarty, A; Nelson, T; Duke, D; Power, C; Hill, A
Abstract: Introduction: Sentinel lymph node biopsy (SLNB) is the gold standard for determining axillary nodal status. There is growing interest in using preoperative axillary ultrasound (AUS) as a non‐invasive means of assessing the axilla. However, AUS has limited sensitivity and is subject to operator dependency. This study aimed to quantify axillary nodal burden in preoperative AUS. Method: This retrospective study used an institutional database of all primary invasive breast carcinomas from 2006–2019. Those with pathologically proven axillary metastatic disease were included. Patients were considered in two groups, low nodal burden/LNB(1‐2LN) and high nodal burden/HNB(≥3LN) based on total positive lymph node count(SLNB+ALND). Preoperative AUS reports were assessed to determine those suspicious for axillary metastasis. Result: Of the 347 patients (n=349 axillae), 77.9% had LNB and 22.1% had HNB. In patients with LNB, 228(83.8%) had a normal AUS versus 44(16.2%) suspicious AUS. In those with HNB 60(77.9%) had normal AUS findings versus 17(22.1%) suspicious findings. On multivariate analysis Nottingham Grade‐3 was associated with suspicious AUS findings (p=0.02). However, receptor status, SLN macro‐metastasis and extra‐nodal extension were not associated with abnormal AUS. Conclusion: As the surgical approach to the axilla becomes increasingly conservative, detection of axillary involvement by non‐invasive means is an area of increasing research. In this cohort, AUS did not reliably identify patients with axillary metastasis. These results highlight the challenges in accurately assessing the axilla using preoperative AUS, which may result in axillary undertreatment if used as an alternative to surgical staging. Take‐home message: As the surgical approach to the axilla becomes increasingly conservative, detection of axillary involvement by non‐invasive means is an area of increasing research. This study highlights the challenges in accurately assessing the axilla using preoperative AUS, which may result in axillary undertreatment if used as an alternative to surgical staging.